THE YIELD OF POTATOES DEPENDING ON THE NORMS OF THE PLANTING AND MASS PLANTING MATERIAL - Кнап Н. В., Н. В.; Гарбар, Л. А. (Scientific Progress & Innovations, 2017)
The results of the research are directed at understanding the influence of norms of planting and mass planting material on productivity formation of potato tubers in the conditions of Transcarpathian region. As a result of our researches it was established that the yield of potatoes varies depending on the mass of planting bubbles and norms of their planting from 39,9 to 58,5 t/ha. By planting tubers weighing 20 g the yield increases with the increase of planting norms, when using tubers weighing 40 and 80 g optimum norms planted are 60–80 thousand pieces/ha.